Canopy Stomatal Conductance Following Drought, Disturbance, and Death in an Upland Oak/Pine Forest of the New Jersey Pine Barrens, USA - Schäfer, Karina V.R. (Frontiers in Plant Science, 2011)
Stomatal conductance controls carbon and water fluxes in forest ecosystems. Therefore, its accurate characterization in land surface flux models is necessary. Sap-flux scaled canopy conductance was used to evaluate the effect of drought, disturbance and mortality of three oak species (Quercus prinus, Q. velutina and Q. coccinia) in an upland oak/pine stand in the New Jersey Pine Barrens from 2005 to 2008. Canopy conductance (GC) was analyzed by performing boundary line analysis and selecting for the highest value under a given light condition. Regressing GC with the driving force vapor pressure deficit (VPD) resulted in reference canopy conductance at 1 kPa VPD (GCref). Predictably, drought in 2006 caused GCref to decline. Quercus prinus GCref was least affected, followed by Q. coccina, with Q. velutina having the highest reductions in GCref. A defoliation event in 2007 caused GCref to increase due to reduced leaf area and a possible increase in water availability. In Q. prinus, GCref quadrupled, while doubling in Q. velutina, and increasing by 50% in Q. coccina. Tree mortality in 2008 led to higher GCref in the remaining Q. prinus but not in Q. velutina or Q. coccina. Comparing light response curves of canopy conductance (GCref) and stomatal conductance (gS) derived from gas-exchange measurements showed marked differences in behavior. Canopy GCref failed to saturate under ambient light conditions whereas leaf-level gS saturated at 1200 µmol m-2 s-1. The results presented here emphasize the differential responses of leaf and canopy level conductance to saturating light conditions and the effects of various disturbances (drought, defoliation and mortality) on the carbon and water balance of an oak-dominated forest.